2019
DOI: 10.2147/ott.s188054
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNA KCNQ1OT1 enhances the chemoresistance of oxaliplatin in colon cancer by targeting the miR-34a/ATG4B pathway</p>

Abstract: Purpose The chemoresistance of colon cancer to oxaliplatin (L-OHP) indicates poor prognosis. Long non-coding RNA (lncRNA) KCNQ1OT1 (KCNQ1 opposite strand/antisense transcript 1) has been shown to participate in the tumorigenesis of several types of cancers. However, little is known about the role of KCNQ1OT1 in the chemoresistance and prognosis of colon cancer. Materials and methods Quantitative-PCR and Western blot were used to measure the expression profiles of KCNQ1O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 49 publications
1
83
0
Order By: Relevance
“…9,20,21 For example, lncRNA KCNQ1OT1 promotes colon cancer chemoresistance through sponging miR-34a and upregulating ATG4B. 24 LncRNA MALAT1 regulates stemness of colorectal cancer cells by interacting with miR-20b-5p to promote Oct4 expression. 25 In addition, lncRNA DGCR5 inhibits HCC cell proliferation and invasion via sponging miR-346 and activating KLF14.…”
Section: Discussionmentioning
confidence: 99%
“…9,20,21 For example, lncRNA KCNQ1OT1 promotes colon cancer chemoresistance through sponging miR-34a and upregulating ATG4B. 24 LncRNA MALAT1 regulates stemness of colorectal cancer cells by interacting with miR-20b-5p to promote Oct4 expression. 25 In addition, lncRNA DGCR5 inhibits HCC cell proliferation and invasion via sponging miR-346 and activating KLF14.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are essential gene modulators that participate in cell cycle, metabolism, survival, inammation, metastasis and drug resistance. [7][8][9] Nuclearenriched autosomal transcript 1 (NEAT1) located at 11q13.1 is a newly emerged oncogene that is involved in the tumorigenesis of a variety of cancers. 10 The dysregulation of NEAT1 is implicated in the poor prognosis of many cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The expression and biological function of KCNQ1OT1 has been investigated in a study by Feng et al, which reported that KCNQ1OT1 expression was elevated in BCa tissues and cells, and the overexpression of KCNQ1OT1 could enhance BCa cell proliferation through the miR-145/CCNE2 pathway (11). In addition, the KCNQ1OT1 has been reported to facilitate the chemoresistance of colon cancer cells (26) and regulate tumor cell proliferation and apoptosis of tongue cancer cells (27). Similarly, our analysis results also detected the upregulated KCNQ1OT1 expression in BCa cells and serum samples, and found the promoting effect of KCNQ1OT1 on BCa cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%